2008
DOI: 10.7589/0090-3558-44.4.864
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genetic Characterization of Porcine Circovirus 2 Isolates From the First Cases of Postweaning Multisystemic and Wasting Syndrome in Wild Boars in Greece

Abstract: ABSTRACT:In 2002, postweaning multisystemic wasting syndrome (PMWS) was diagnosed in a European female wild boar (Sus scrofa), based on the detection of porcine circovirus 2 (PCV2) DNA in various organs, including the uterus, and on histopathologic lesions. This is the first detection of PCV2 DNA in the uterus of a wild boar. Three years later (2005), a wild boar ,6-8 mo of age was found moribund. It presented wasting and dyspnea and finally died. PCV2 DNA was detected in tissue samples, and histopathologic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…In Hungary, some isolates had the closest relationship with a Canadian isolate, and the others were similar to a German isolate. In Greece, Sofia et al (2008) showed that the two Greek strains from wild boars were closely related to each other and were clustered with two isolates from wild boars from Hungary. Csagola et al (2006) and Sofia et al (2008) postulated that observed genetic similarities suggest an epidemiologic link between wild boar and domestic pig populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Hungary, some isolates had the closest relationship with a Canadian isolate, and the others were similar to a German isolate. In Greece, Sofia et al (2008) showed that the two Greek strains from wild boars were closely related to each other and were clustered with two isolates from wild boars from Hungary. Csagola et al (2006) and Sofia et al (2008) postulated that observed genetic similarities suggest an epidemiologic link between wild boar and domestic pig populations.…”
Section: Discussionmentioning
confidence: 99%
“…In Greece, Sofia et al (2008) showed that the two Greek strains from wild boars were closely related to each other and were clustered with two isolates from wild boars from Hungary. Csagola et al (2006) and Sofia et al (2008) postulated that observed genetic similarities suggest an epidemiologic link between wild boar and domestic pig populations. However, in recent studies, no direct evidence was found for PCV2 transmission between domestic pig and wild boar (Reiner et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PCV2 infection was detected in about 20% of Hungarian wild boars using polymerase chain reaction (PCR) (7). In Greece, there was a report stating that wild boars with wasting and dyspnea had died and PCV2 was detected in tissue samples and the histopathologic lesions were consistent with PMWS described in domestic pigs (10). In Brazil, a high (54.09% to 89.53%) prevalence was reported (2) The samples of the two animals were positive for PCV2 and the complete PCV2 genome was sequenced from the two samples using four pairs of primers described by An (1).…”
mentioning
confidence: 78%